Evaluation and management of acute epistaxis in the emergency department - Abduljabbar, Ashraf Abdulaziz; Abdulmahdi, Abdulla Khalaf; Alalshojaa, Asma Yahia; Alfaier, Mohammed Qhalib; Almasuai, Ahmed Hassan; Alfadley, Abdulaziz Fadel; Alkanderi, Roaa Ali; Alyousif, Amal Yasir; Alabdullatif, Ghaith Saleh; Almuaddi, Abdulrahman Saeed; Alkurdi, Abdullah Ahmad (International Journal Of Community Medicine And Public Health, 2023)
Acute epistaxis, or nosebleed, is a common presentation in the emergency department (ED) that requires a systematic evaluation and prompt management. The assessment involves considering the severity of bleeding, identifying underlying causes, and implementing appropriate interventions. Modifiable risk factors, such as medication review, nasal hygiene, avoidance of nasal trauma, and humidification, should be addressed to prevent recurrence. Referral to specialists is necessary for cases of recurrent or severe bleeding, suspected underlying causes, or inadequate response to initial management. Collaboration between ED healthcare providers and specialists ensures comprehensive evaluation, specialized interventions, and long-term management. Regular follow-up appointments and patient education are essential for monitoring progress, adjusting treatment, and preventing complications. By employing a comprehensive approach, healthcare providers aim to alleviate distress, achieve hemostasis, identify underlying etiologies, and optimize patient outcomes in the ED.